PERLINDUNGAN HUKUM TERHADAP DATA PRIBADI NASABAH DALAM LAYANAN INTERNET BANKING - Wulan Pradnyasari, Gusti Ayu Putu; Mahartayasa, Made (Kertha Semaya : Journal Ilmu Hukum; Vol. 02, No. 04, Juni 2014, 2014)
A paper entitled "Legal Protection of Customers’’ Personal Data Who Use Internet Banking Service" has a purpose that to know how the legal protection of customers’ Personal Data who use Internet Banking service is. Internet Banking is a service created by banks (private and government) to take advantage of Internet technology, as a medium to perform a variety of transactions related to banking transactions. The research method used in this study is a normative study. The conclusion of this paper is the legal Protection of customers' personal data can be performed with the approach of self-regulation and government regulation in the article 29 paragraph (4) and Article 40 paragraph (1) and (2) of Law Number 10 of 1998 concerning to the amendment of Law Number 7 of 1992 concerning Banking. Repressive legal protection stipulated in Bank Indonesia Regulation (PBI) No. 7/7/PBI/2005 jo Bank Indonesia Regulation (PBI) No. 10/10/PBI/2008 on Resolving Customer Complaints, Bank Indonesia Regulation (PBI) No. 8/5/PBI/2006 jo Bank Indonesia Regulation (PBI) No. 10/1/PBI/2008 About Mediation Banking, and article 21 paragraph (2) A, (2) B, (2) C, (3), (4), (5) and article26 paragraph (1) and (2) of Law No. 11 of 2008 on Information and Electronic Transactions has been set regarding the protection of personal data of customers who use Internet Banking Service.
Keywords: Internet Banking, Legal Protection, Personal Data